Analisis Pengaruh Faktor Makroekonomi terhadap Return dan Risk Premium Saham Menggunakan Model Arbitrage Pricing Theory - Zunara, Elly; Hartoyo, Sri (Universitas Brawijaya, Indonesia, 2016)
Stock is one of the most popular monetery market instrument and the alternative interesting investation in capital market because it may given the high return to the investor. The price of stock is fluctuative because the comuditythat is sensitive changeable based on the internal and external factors of a company. There are existence of fluctuations of stock that make the investor focus on expected return levelon the investments made as compensation for the risks to be faced.APT (Arbitrage Pricing Theory) model improved by Stephen A Rose is one of the developerin CAPM (Capital Asset Pricing Theory) to determining the expected return in the market. Some experts claim that APT model is better than CAPM because the price of stock is not only determined by single market index but also by many macroeconomics factors. Based on the explanation above, the researcher will research the return and risk premium in stock exchange of Indonesia using APT model. It will be found the macroeconomic factors that may affectstock return and premium risk in APT Model, such as the level of inflation, Rupiah rate exchange to US dollars, and the price of world oil.